Physical and Chemical Properties of Ensiled Safflower (Carthamus tinctorius L.) Cultivars at Three Development Stages - Yüksel, O; Bıçakçı, E; Arslan Duru, A; Duru, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to assess the physical and chemical properties of silages made from six safflower cultivars, harvested at three distinct development stages in Türkiye in 2020. The safflower cultivars were ensiled without additives during the budding, blooming, and seed-filling stages, with three replications. The study evaluated the physical characteristics and DLG scores of the silages, alongside measurements of dry matter content (DM), pH, Fleig score (FS), crude protein (CP), crude fat (CF), crude ash (CA), neutral detergent fiber (NDF), acid detergent fiber (ADF), digestible dry matter (DDM), dry matter intake (DMI), and relative feed value (RFV). The results revealed no statistically significant difference (p>0.05) in the physical properties, DLG score, and pH values among the safflower silages. However, significant differences (p<0.05) were observed in the DM (33.96% to 40.20%), CF (1.28% to 2.3%), CA (8.44% to 9.17%), NDF (43.40% to 47.44%), ADF (32.32% to 33.18%), DDM (60.72% to 63.75%), DMI (2.53% to 2.77%), and RFV (153.74 to 176.79) values across the different safflower cultivars. Advancing development resulted in increased DM content (24.62% to 48.00%), FS (80.01 to 131.50), CA content (1.12% to 3.03%), NDF content (43.04% to 47.62%), and ADF content (32.86% to 35.12%). Conversely, it led to decreases in CP content (14.66% to 7.65%), CA content (11.14% to 6.56%), DDM content (63.30% to 61.55%), DMI (2.80% to 2.53%), and RFV (177.10 to 155.49). In conclusion, all safflower cultivars demonstrated commendable relative forage values (RFV), with the Olas and Linas cultivars exhibiting superior performance compared to the others. From a harvest management standpoint, ensiling at the budding stage is identified as the most effective practice.